Pengaruh Metode Demonstrasi dengan Media Tutup Botol terhadap Hasil Belajar Tematik Siswa Kelas I SDIT Budi Utomo Makassar - Nurhayati Selvi; Wahyullah Alannasir (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
There are many learning methods that can be applied to achieve success in learning. The purpose of this study was to describe the application of the demonstration method with bottle cap media and how much influence the application of the method had on the learning outcomes of first grade students of SDIT Budi Utomo Makassar. Quantitative research approach, the type of experiment with Pre-Experimental Design (nondesign) with the form of One-Shot Case Study research. This research is located at SDIT Budi Utomo Makassar with a population of grade I students for the 2020/2021 academic year. The sampling technique used purposive sampling, so the sample was 21 students. Data collection techniques: tests, observations and documentation. Analysis technique: Descriptive and inferential statistics, paired sample T-Test hypothesis testing. The results showed that teachers used used bottle caps as a medium in the implementation of the demonstration method. This activity stimulates students to think about solving problems that contain puzzles so as to encourage students to be interested in paying attention to the demonstration activities. The application of the demonstration method with bottle cap media has an effect on learning outcomes for class I students at SDIT Budi Utomo Makassar.